2020
DOI: 10.3390/pharmaceutics12010033
|View full text |Cite
|
Sign up to set email alerts
|

Stencil Printing—A Novel Manufacturing Platform for Orodispersible Discs

Abstract: Stencil printing is a commonly used printing method, but it has not previously been used for production of pharmaceuticals. The aim of this study was to explore whether stencil printing of drug containing polymer inks could be used to manufacture flexible dosage forms with acceptable mass and content uniformity. Formulation development was supported by physicochemical characterization of the inks and final dosage forms. The printing of haloperidol (HAL) discs was performed using a prototype stencil printer. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Therefore, it can be conferred that ENRG 0.83 and ENRG 0.86 are the most suitable formulations for fabricating stencil printed sensors. Further scrutinizing the requirement for stencil printing indicated that a higher value of complex viscosity at a lower frequency indicates better stencil printability . Considering the observations made from the rheological studies (both from frequency and amplitude sweep) and the printability index parameter, it can be unequivocally suggested that ENRG 0.86 demonstrated a strong dominancy of the elastic component and can be considered as a potential candidate for stencil printing.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, it can be conferred that ENRG 0.83 and ENRG 0.86 are the most suitable formulations for fabricating stencil printed sensors. Further scrutinizing the requirement for stencil printing indicated that a higher value of complex viscosity at a lower frequency indicates better stencil printability . Considering the observations made from the rheological studies (both from frequency and amplitude sweep) and the printability index parameter, it can be unequivocally suggested that ENRG 0.86 demonstrated a strong dominancy of the elastic component and can be considered as a potential candidate for stencil printing.…”
Section: Resultsmentioning
confidence: 97%
“…Further scrutinizing the requirement for stencil printing indicated that a higher value of complex viscosity at a lower frequency indicates better stencil printability. 44 Considering the observations made from the rheological studies (both from frequency and amplitude sweep) and the printability index parameter, it can be unequivocally suggested that ENRG 0.86 demonstrated a strong dominancy of the elastic component and can be considered as a potential candidate for stencil printing. The plot of G′/G″ for other samples (ENRG 0.24, ENRG 0.49, ENRG 0.72, and ENRG 0.76) is shown in Figure S4b.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The results show that the drug was amorphous after printing and the pH remained above pH 4. Disintegration studies showed that the orodispersible discs printed showed disintegrations times below 30 s. Therefore, it was concluded that the novel method of batchwise stencil printing, could be used as a viable method for the production of pharmaceuticals [17].…”
Section: Stencil Printingmentioning
confidence: 99%
“…10,29 Added to the very short cycle times (\ 3 s), it becomes evident that the adhesive rheological properties must be optimized and precisely adjusted to meet all these requirements. Typically measured rheological properties for the printing process are the shear-dependent viscosity, 21,23,[29][30][31] yield stress, 21,24,31 viscoelasticity, [21][22][23]29,30 thixotropic behaviour 13,[29][30][31][32] and extensional behaviour. 22,24,30,31 These properties should be adjusted to facilitate the adhesive aperture filling and separation from the stencil, avoiding unwanted effects, such as filament stretching, 22,24,25 spreading, 24,33 superficial irregularities 10 and bubbles.…”
Section: Introductionmentioning
confidence: 99%